Técnicas de inoculación a campo Aspergillus flavus en maíz, Córdoba - Cordes, Diego Darío; Camiletti, Boris Xavier; Gimenez, Maria De La Paz; Torrico Ramallo, Ada Karina (Asociación Argentina de Fitopatólogos (AAF), 2024)
Poster